Study Planning of the Dwi Indah Building Pile Foundation in Selodono Village, Kediri Regency - Galang Santoso; Edy Gardjito; Agata Iwan Candra; Romadhon Romadhon; April Gunarto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2021)
Foundation is a structure that functions to withstand loads above it and the load itself. These loads are transferred to the ground directly. The case study in this plan is the construction of the Dwi Indah Building in Selodono Village, Kediri Regency. The building has a building area of 308 m2 and a height of 16 m, with the function of the building as an inn. In this planning, the type of pile foundation is used. A Pile foundation is a type of deep foundation that divides the gravity load evenly on the ground and makes the structure of the building strong and strong. The purpose of this planning is to plan a strong pile foundation that is able to withstand the load of the Dwi Indah Building. The method used in this planning is the Meyerhoff method, with a pile diameter of 30 cm and a foundation depth of 800 cm. From the calculation results obtained (single pile bearing capacity) Pall= 42.62 tonnes greater than (maximum pile load) Pmax= 26.00 tonnes (SAFE). For the control of the yield of the buckling factor, the result is (buckling) ω= 178.61 kg/cm2 <(base stress) σ = 2400 kg/cm2 (SAFE).